JIHAD DAN RADIKALISME MENURUT QURAISH SIHAB DAN SAYYID QUTHB - Bustami Saladin (Research Institute and Community Engagement of IAIN MADURA, 2018)
Al- Qur’an is a guidance for us. Al- Qur’an is a source of all kinds of regulations and laws. Literally Jihad comes from the Arabic word “Juhdun” which means a power and “Jahada” which means an “effort”. It can be concluded that the meaning of Jihad is an effort to reach the truth as it is believed with all ability and personal strength. The term “radical” comes from Latin word “radix, radic is”, the Indonesian dictionary gives the meaning of “totally”, “all-out”, “ very strong in asking for changes”, and “progressive in thinking and acting”.